Treatment with Recombinant Enzymes Pbserum Medical High in a Patient Post Skin Grafts for Burns on the Right Lower Limb (London Journal of Medical and Health Research, 2024)
Burns on the skin and their treatment have been considered a medical issue since ancient times. Approximately 90% of burns are of thermal origin, all of which involve tissue destruction. The depth and extent of the burn are important factors to consider when treating the injury. Frequently, the resulting wounds are impossible to close or suture primarily, necessitating coverings such as grafts to achieve a stable and durable solution. However, these burns and their grafts can lead to pathological scars, which can have negative consequences for the individual, both aesthetically and physiologically, as they can impair proper movement of the affected limb. These scars are characterized by excess collagen deposition, making the use of the enzyme collagenase, which degrades this protein, relevant. Pbserum is a treatment line based on high molecular weight hyaluronic acid (HA) and a novel recombinant enzymatic system composed of collagenase, lipase, and liase. We present a case of a patient post skin grafts for burns on the right lower limb treated with High pbserum enzymes. This enzymatic cocktail proved to be safe and effective and resulted in the satisfactory evolution of the patient from the first application. Its benefits were improvement in pigmentation and skin appearance, reduction of hypertrophic areas, and a more normal gait pattern, enabling a return to daily activities and significantly improving quality of life.
Keywords: enzymes.; Burns; hypertrophic scars; skin grafts; collagenase; recombinant.